Black, Radical, and Campesino in Revolutionary Cuba. Issue 4 (2nd October 2019) - Kozameh, Sara
Abstract : In 1959, Cuba's Revolutionary leaders passed a sweeping Agrarian Reform. This article focuses on a group of black radical peasant organizers, many of them Communists, in order to rethink the origins of the revolutionary project. Based on oral histories, archival documents, and testimonial narratives, this article decenters Cuba's revolutionary leaders to recover the lost stories and victories of black radicals who laid the groundwork for one of the revolution's most socially, economically, and politically transformative measures and whose long-held commitment to socialism and agrarian justice made an early and deep impact on the origins and course of the Cuban Revolution.